A closed-loop feedback simulation for RFID-based manufacturing planning and control system. (1st January 2013) - Wang, Li-Chih; Cheng, Chen-Yang; Hsu, Shih-Lun
Nowadays, the performance of customer service level in manufacturing industries highly depends on an effective manufacturing planning and control system (MPCS). An agent-based manufacturing planning and control system (AMPCS) allows negotiation-based decision-making to achieve the global objective. With the advantage of radio frequency identification (RFID) technology, agents in AMPCS may effectively control and identify the production progress of all raw materials, work-in-progress (WIP), and products across the entire manufacturing supply chain. However, the production schedule may become inefficient or even infeasible due to uncertainties, such as machine breakdowns, processing time delays, rush order, quality problems, and unavailable material. Therefore, this research proposes a closed-loop feedback simulation (CLFS) approach based on RFID-enabled real-time manufacturing information for scheduling and rescheduling in an agent-based manufacturing system in response to the dynamically changing manufacturing activities and exceptions. From the simulation experiment, the scheduling results proposed by RFID-based MPCS combined with CLFS performed much better than the results obtained from previous researches.